Identification of Chrysanthemum (Chrysanthemum morifolium) Self-Incompatibility. (31st December 2013) - Wang, Fan; Zhang, Feng-Jiao; Chen, Fa-Di; Fang, Wei-Min; Teng, Nian-Jun
Abstract : There has been a heated argument over self-incompatibilityof chrysanthemum ( Chrysanthemum morifolium ) among chrysanthemum breeders. In order to solve the argument, we investigated pistil receptivity, seed set, and compatible index of 24 chrysanthemum cultivars. It was found that the 24 cultivars averagely had 3.7–36.3 pollen grains germinating on stigmas at 24 hours after self-pollination through the fluorescence microscope using aniline blue staining method. However, only 10 of them produced self-pollinated seeds, and their seed sets and compatible indexes were 0.03–56.50% and 0.04–87.50, respectively. The cultivar "Q10-33-1" had the highest seed set (56.50%) and compatible index (87.50), but ten of its progeny had a wide range of separation in seed set (0–37.23%) and compatible index (0–68.65). The results indicated that most of chrysanthemum cultivars were self-incompatible, while a small proportion of cultivars were self-compatible. In addition, there is a comprehensive separation of self-incompatibility among progeny from the same self-pollinated self-compatible chrysanthemum cultivar. Therefore, it is better to emasculate inflorescences during chrysanthemum hybridization breeding when no information concerning its self-incompatibility characteristics is available. However, if it is self-incompatible and propagated by vegetative methods, it is unnecessary to carry out emasculation when it is used as a female plant during hybridization breeding.